BASIC PRINCIPLES OF MODEL BUILDING FOR COMPETITIVE WORKFORCE TRAINING AT INDUSTRIAL ENTERPRISES - V. A. Fedorov; S. V. Vasiliev (Russian State Vocational Pedagogical University, 2015)
The research is devoted to theoretical substantiation, development and approbation of effective approaches, principles and conditions of in-service training at industrial enterprises. The research methods include the analysis of scientific publications and effective vocational training expertise, modeling, inclusive monitoring, questionnaires and expert assessment. The author proposes the organizational and educational principles of corporate vocational training of competitive workmen; the above principles and conditions were analyzed based on the competence, module and sociocultural approaches. The model approbation, exemplifying the effective training for the welder occupation, was carried out at plc Uralvagonzavod. The research findings can be used for developing the policy of continuing education at industrial enterprises, corporate universities and training centers; they also provide the methodology basis for further investigation of vocational training problems.